Problem Based Learning Model to Increase Junior High School Students Achievement Motivation - Sukriyatun, Gunarti; Mujahidin, Endin; Tanjung, Hendri (Technium Social Sciences Journal, 2023)
This research aims: 1) to determine current achievement motivation junior high school students in Bogor City. 2) to develop Problem Based Learning model to improve students of junior high school in Bogor City. 3) to determine the effectiveness of PBL model in improving students of junior high school achievement motivation and innovation in Bogor City. This research is based on the development research by Borg and Gall with three research and development stages, preliminary study, model development, and model test. The data analysis used during the development research were descriptive analysis, model validation analysis, and model effectiveness analysis with t-test independent samples. The results of the research concluded that: the achievement motivation and innovation of junior high school students in Bogor City is currently low and needs to be improved; the developed model is declared "fit for use" by learning experts with more notes. The PBL model is declared effective in increasing the achievement motivation students for junior high school in Bogor City.